(untitled) (European Journal of Behavioral Sciences, 2024)
Informal mental health carers play a crucial role in supporting individuals with depression and anxiety. However, there is a lack of knowledge on how to effectively support these carers and promote their well-being. This mixed-method study aimed to explore the support needs of carers of a person with depressive or anxiety symptoms, living in Australia. Sixty-seven carers (female 76 %, median age 48) completed an online survey, and 22 completed semi-structured interviews about their support experiences. Over half of the survey respondents reported high levels of psychological distress on the Kessler Psychological Distress Scale (K10), and 63% reported understanding and adjusting to the caregiving role as the most needed areas of support, as identified on the Caregiver Perspective Questionnaire (CPQ). Through thematic analysis of the interviews, four key themes emerged describing carers’ support experiences and needs: connecting with formal services, responding to the care-recipient, connecting socially, and caring for the self. The analysis also found that time constraints and stigma can be significant support barriers for these carers. This is the first time that a study has investigated the support experiences and needs of carers of a person with depressive or anxiety symptoms, living in Australia. The findings contribute to current literature on mental health carers and offer novel and tangible insights into future research and support opportunities.